Help! Somebody get me out of fourth grade! - Winkler, Henry, 1945- (Winkler, Henry, 1945- Hank Zipzer, 2004)
Fearing that he may be failing fourth grade, Hank enlists the help of his friends, and even his annoying younger sister, in an effort to prevent his parents from attending a parent-teacher conference.